2023
DOI: 10.1111/sode.12668
|View full text |Cite
|
Sign up to set email alerts
|

Siblings in lockdown: International evidence for birth order effects on child adjustment in the Covid19 pandemic

Abstract: Supportive family relationships may mitigate the impact of the Covid19 pandemic on young children's adjustment, but existing work is limited by its focus on within‐country variation and parental influences. Addressing these gaps, and drawing on reported buffering effects of older siblings on child mental health (Lawson and Mace, 2010), the current international study examined whether child adjustment problems were, on average, elevated by the pandemic and whether this buffering effect of older siblings would b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 103 publications
(103 reference statements)
1
1
0
Order By: Relevance
“…A recent study also discovered that children with more than two siblings have fewer emotional and behavioural problems than children with only one sibling. In line with Hughes and Ronchi [ 43 ], children with one or more older siblings had more emotional and behavioural problems than children without siblings. One possible explanation is that healthy sibling relationships can be a tremendous source of support, promote empathy, and ensure that siblings have a strong support system, which helps them avoid developing mental health challenges themselves.…”
Section: Discussionsupporting
confidence: 78%
“…A recent study also discovered that children with more than two siblings have fewer emotional and behavioural problems than children with only one sibling. In line with Hughes and Ronchi [ 43 ], children with one or more older siblings had more emotional and behavioural problems than children without siblings. One possible explanation is that healthy sibling relationships can be a tremendous source of support, promote empathy, and ensure that siblings have a strong support system, which helps them avoid developing mental health challenges themselves.…”
Section: Discussionsupporting
confidence: 78%
“…We find that, on average, a higher sentiment score is associated with higher perceived returns, particularly for play with friends; on the other hand, we do not find any systematic relationship between the sentiment score and perceived risks (Appendix Table B8). 23 This result aligns well with recent evidence on the key role of parental mental well-being in explaining investment decisions in children (Baranov, Bhalotra, Biroli, and Maselko (2020)), and is consistent with research in clinical psychology showing that, by distorting beliefs, mental health can affect the way people think and behave (Gotlib 22 Concerns about the child social development are not uncommon: for example, Byrne et al (2022) document worsening social communication skills in children born during the lockdown as compared to a historical cohort in Ireland, on the basis of parental reports; Hughes et al (2023) find that children with siblings are able to adjust better to lockdown restrictions. 23 The table report results by terciles of the empirical distribution of the sentiment score.…”
Section: Characterizing Parental Beliefs Using Text Datasupporting
confidence: 69%
“…It could be assumed that the presence of siblings acts in a similar way. The only child status has emerged as a risk factor for cognitive and socio-emotional development [ 74 , 75 , 76 , 77 ]. Previous studies have revealed that only children exhibit more positive developmental outcomes, more positive relationships with their parents, and fewer behavioral problems in school compared with non-only-children [ 75 , 78 ].…”
Section: Discussionmentioning
confidence: 99%